Experimental Study on The Capacity Of Z-Brace and X-Brace Cold-Formed Steel Wall Panel - Cantikawati, Khristia Ningsih; Nindyawati, Nindyawati; Sulaksitaningrum, Roro (Jurnal Teknik Sipil dan Perencanaan, 2023)
Awaludin et al. created an anti-earthquake temporary shelter called RISBARI (Rumah Instan Baja Ringan/Light Steel Instant House), featuring an X-shaped strap-braced wall system using cold-formed steel as its primary structure. A similar temporary shelter (hunian sementara/huntara) was developed by Biru Bumi Hijau using Z-shaped wall bracing. While experimental research on the lateral strength of cold-formed steel wall panels with X-brace bracing, such as in RISBARI, has been conducted extensively, there has been limited in-depth study on Biru Bumi Hijau's huntara. Hence, this research aimed to identify the load capacity, stiffness, and ductility of both bracing configurations on lateral strength using cold-formed steel wall panels. This study used an experimental method through the monotonic static load in the laboratory. The test results were analyzed with One-way ANOVA. The load capacity, stiffness, and ductility of the X-brace panel increased by 201%, 4452%, and 105%, respectively. In contrast, the load capacity, stiffness, and ductility of the Z-brace panel increased by 201%, 4253%, and 156%. The bracing capacity on both was not directly proportional since both test objects had different configuration structures, although they had equalized length and width.